Can Routine Histopathology Distinguish Between Vulvar Cutaneous Candidosis and Dermatophytosis?. Issue 3 (July 2016) - Day, Tania; Borbolla Foster, Ailsa; Phillips, Samuel; Pagano, Ross; Dyall-Smith, Delwyn; Scurry, James; Garland, Suzanne M.
Abstract : Objectives: This study aimed to determine if vulvar cutaneous candidosis and dermatophytosis can be distinguished by routine histopathology. Materials and Methods: Twenty-four cases of periodic acid-Schiff–stained vulvar biopsies with a diagnosis of cutaneous mycosis were reviewed and histopathological characteristics on both periodic acid-Schiff and hematoxylin and eosin were recorded. Data were collected on age, clinical impression, microbiological results, and treatment, and all specimens underwent multiplex polymerase chain reaction analysis. Results: The mean age was 60 years, and all but 3 women had at least 1 risk factor for mycosis including 15 (62.5%) with lichen sclerosus and/or planus managed with topical corticosteroids. A clinical suspicion of tinea or candidosis was documented in 12 (50%) of the cases. Vulvovaginal swabs showed Candida species in 9 women; one skin scraping was positive for Trichophyton rubrum . Microbiology was not obtained in 8 patients, 5 had a negative swab, and 1 had negative skin scrapings. No histopathological or morphological features distinguished Candida species from dermatophytes. Organisms appeared as basophilic structures in the stratum corneum in 15 (62.5%) hematoxylin and eosin–stained slides. Polymerase chain reaction results were positive for Candida species in 5 (21%) and for dermatophytes in 3 (13%), negative in 13, and unassessable in 3 cases. Conclusions: Vulvar cutaneous candidosis and dermatophytosis cannot be reliably distinguished by routine histopathology or specific polymerase chain reaction. A high index of suspicion combined with adequate microbiological testing remains the best approach to differentiating between the 2, which impacts on counseling, treatment, and prognosis. Abstract : Vulvar cutaneous candidosis and dermatophytosis cannot be reliably distinguished by routine histopathology or polymerase chain reaction.